Abu Thanâ' Shihâbuddîn Al-Alûsî's Interpretation of the Self-Harm (Ẓālim Li Nafsih) Verses - Amalia, Ilma; Komarudin, Edi (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
This study explores Abu Thanâ' Shihâbuddîn Al-Alûsî's interpretation of Qur'anic verses addressing self-harm (ẓālim li nafsih) and its relevance to the modern phenomenon of self-inflicted harm. Using a qualitative, descriptive-analytical method, the research examines Al-Alûsî's tafsir in Rūh al-Ma'ānī, particularly regarding verses such as Qs. Al-Baqarah: 195, Qs. Ali-Imran: 117, and others. Al-Alûsî interprets ẓālim li nafsih as actions violating divine commands, encompassing spiritual, moral, and physical dimensions. He emphasizes that such acts result in self-inflicted harm both in this world and the hereafter. The research draws parallels between ẓālim li nafsih and self-harm, illustrating how the latter reflects a crisis of spirituality and morality. Al-Alûsî highlights the importance of repentance, spiritual reflection, and maintaining a strong relationship with Allah SWT to heal spiritual wounds caused by self-harm. His interpretation underscores the Qur'an's guidance for addressing internal struggles through a holistic approach combining spiritual, social, and moral support. The study concludes that Al-Alûsî's insights provide a meaningful framework for understanding and addressing self-harm within an Islamic context, offering hope and a path to redemption for individuals affected by this issue.